The prevalence of type 2 diabetes mellitus in the adult population of Russia (NATION study) - Ivan I. Dedov; Marina V. Shestakova; Gagik R. Galstyan (Сахарный диабет, 2016)
Aim. To estimate the prevalence of type 2 diabetes mellitus (T2DM) in Russian adults.Materials and methods. NATION was a national, epidemiological, observational, cross-sectional study. The sample of adults (20–79 years old) was stratified by age, sex, geographic region and settlement type to obtain a representative sample. Recruitment was performed in public areas with large number of people. T2DM was diagnosed by glycated haemoglobin A1c (HbA1c) levels (diabetes: HbA1c≥6.5%; pre-diabetes: HbA1c≥5.7% to <6.5%). Socio-demographic and anthropometric data were collected.Results. Blood samples from 26,620 subjects were available. Overall, 5.4% were diagnosed with T2DM (2.5% were previously diagnosed and 2.9% were previously undiagnosed); 19.3% were pre-diabetic. T2DM prevalence increased with age (up to 70 years), and no significant difference was revealed between females and males (5.6% vs. 5.1%). The estimated prevalence of pre-diabetes and T2DM tended to increase with increasing BMI. T2DM prevalence varied by geographic region and was higher in rural areas than in urban areas (6.7% vs. 5.0%, p < 0.001).Conclusion. Approximately one in five adult Russians had pre-diabetes, 5.4% had T2DM and about half of the diabetic subjects were previously undiagnosed. These results demonstrate the need for new programs in the Russian Federation to predict, prevent and manage T2DM.